Dissemination of Agricultural Technologies through Mobile Message Service in Karnataka - N. Shankaraiah,; B.K. Narayana Swamy,; S.C. Shashekala,; P. Ravikumar, (Journal of Agricultural Extension Management, 2025)
The mobile phone technology is being used creatively to help spur development and reduce poverty, particularly in remote rural areas. A research study was undertaken to know the Agricultural Technologies disseminated through Mobile Message Service (MMS) and also to study the constraints faced by farmers in using the service. The study was conducted at Doddaballapur taluk of Bangalore Rural District of Karnataka during 20 10-1 1. The respondents were 40 farmers selected using simple random sampling technique. Findings indicated that Agricultural technologies on crop management, marketing, Horticultural technologies on tissue culture, floriculture, veterinary technologies on dairy, poultry and others on weather information were rated, as more relevant technologies disseminated through the MMS network